2015
DOI: 10.5812/ircmj.23492v2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motivational Interviewing on a Weight Loss Program Based on the Protection Motivation Theory

Abstract: Background:The prevalence of overweight and obesity is on the increase the world over, which imposes an ever-increasing burden on societies and health care systems.Objectives:This study sought to investigate the effect of motivational interviewing (MI) on a weight-loss program based on the protection motivation theory (PMT).Patients and Methods:This randomized clinical trial study, comprising pretest-posttest with a control group, was conducted on 150 overweight and obese women attending a private nutrition cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Attitude was the strongest predictor of intention in our survey after 6-months follow-up, which might be explained by the fact that attitude change requires a long time compared to other constructs. Mirkarimi et al (19) and Park et al (25) reported that perceived selfefficacy and response efficacy were the strongest predictors of women's intention to follow weight-loss programmes and intention toward functional food consumption, which is similar to our present findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Attitude was the strongest predictor of intention in our survey after 6-months follow-up, which might be explained by the fact that attitude change requires a long time compared to other constructs. Mirkarimi et al (19) and Park et al (25) reported that perceived selfefficacy and response efficacy were the strongest predictors of women's intention to follow weight-loss programmes and intention toward functional food consumption, which is similar to our present findings.…”
Section: Discussionsupporting
confidence: 92%
“…This might have been caused by 2 different samples in our study (obese and overweight women) and in theirs (pregnant women). Mirkarimi et al (19) also revealed that all constructs of the PMT were changed significantly after intervention in the motivational interviewing and motivation-intention groups compared to the control group. A meta-analysis of weight-loss interventions exploring diet only with diet and PA reported medium changes of 1.64 kg or 1.24 kg/m 2 after a combination of dietary and augmented PA (28).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PMT was developed by Rogers in 1975 to describe behavioral and attitudinal processes taken by people when facing perceived reality or health threat (19). PMT describes factors that play important roles in individuals' motivation for doing or not doing a sanitary behavior (20).…”
Section: Introductionmentioning
confidence: 99%
“…RCT on three groups of 150 obese (BMI 29-35 kg/m 2 ) Iranian females also indicated MI effectiveness. One of two groups with MI (5 MI group sessions with a psychologist and 4 sessions on diet and exercising) had additional goal and deadline establishment, and obtained a higher anthropometric status in a 2-month follow-up (the control group showed weight loss only directly after the sessions) [15]. Another Iranian single-blind RCT on 100 obese (BMI 25-35 kg/m 2 ) women showed high MI effectiveness after five sessions delivered for a 7-10-participant group with the provision of pamphlets on overweight and obesity as well as advantages of diet change.…”
Section: In Overweight and Obesitymentioning
confidence: 99%